200k views
4 votes
Use the elimination method to solve the following system of equations.

3x - y = 1

-2x + y = 2

Show the steps used to solve this problem.

1 Answer

3 votes

Notice -y in the first equation and y in the second equation. If you add -y to y, you get zero, and the y variable is eliminated. We add the equations to use the elimination method and eliminate y.

3x - y = 1

-2x + y = 2

Add equations to get

x = 3

Now that we have x = 3, we substitute 3 for x in the first equation and solve for y.

3(3) - y = 1

9 - y = 1

-y = -8

y = 8

Solution: x = 3; y = 8

User Kovan
by
5.2k points